LARANGAN MENGIKUTI HAWA NAFSU DALAM KAJIAN TEMATIK DIGITAL QURAN - Nofitayanti Nofitayanti; Udin Supriadi (ZAD Al-Mufassirin, 2020)
This research is a literature study using the Digital Quran application that discusses the prohibition of following lust to regrow scientific treasures about nafs. In this study discussed include: Understanding nafs, sharing nafs and presenting the quran's digital thematic study of nafs. Based on the results of research on the Digital Thematic Method of the Quran, the word lust in the Quran there are as many as 35 verses in the Indonesian term and 8 verses with the Arabic term of the word (النفس). In general it can be said that nafs in the context of talk about humans point to the inner side of humans that are potentially good and bad. Nafs was created by God in a perfect state as a device in man's spiritual, created completely to him good and bad so that he could know what was good and what was bad and man was given the power to choose between the two.